O uso de luvas pela equipe de enfermagem em ambiente hospitalar - Rio, Caroline do (Universidade Federal de São Carlos, 2020)
Objective: to characterize the adhesion of the nursing team to the use of gloves in the hospital setting. Methods: a descriptive exploratory study with a quantitative approach, where between August and October 2019, the use of gloves by the nursing team was observed in the performance of 396 procedures, in a hospital in countryside of São Paulo State of, Brazil. All ethical aspects were considered. Results: 32 different types of procedures were observed. Regarding hand hygiene, only 1.76% (7) was performed before the procedure and only 4.54% (18) after the procedure. The rate of adherence to the correct use of gloves was 60.1% (238). In other 39.9% (158) opportunities, incorrect use varied between reuse (18.43%), unnecessary use (8.33%) and non-use being necessary (13.13%). Conclusion: the use of gloves by the nursing team showed non-conformities in 39.89% of the times. The need for reflection is reinforced with teams and managers that go beyond knowledge assessment and availability of inputs.
Gloves use by nursing team in a hospital setting
Keywords: Uso de Luvas; Equipe de Enfermagem; Infecção Hospitalar; Protective Gloves; Nursing team; Nosocomial Infection; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE DOENCAS CONTAGIOSAS